Epstein-Barr Virus Infection in an Elderly Nonimmunocompromised Adult Successfully Treated with Rituximab - Jacob P. Smeltzer; Matthew T. Howard; Wilson I. Gonsalves; Thomas E. Witzig (Case Reports in Hematology)
Epstein-Barr virus (EBV) is a ubiquitous virus that commonly affects children and adolescents. In addition to causing a viral illness, it is also associated with various malignancies in particular B cell lymphomas and lymphoproliferative disorders. Differentiating between the two processes can be a diagnostic challenge. Here, we present a case of an atypical EBV infection in an elderly patient with severe systemic symptoms, multiorgan involvement, lymphadenopathy, and negative EBV serology. Excisional lymph node biopsy demonstrated features of a lymphoproliferative process involving EBV. Despite supportive care, she experienced continued clinical deterioration and was successfully treated with rituximab. This case illustrates the diagnostic challenges of these cases particularly in the elderly who may have age related immunosenescence, the utility of EBV PCR testing, and the clinical efficacy of rituximab in clearing the infected cells.